Analysis of the stress and directional dependent Bauschinger-effect of sheet metals - Rosenschon, Martin; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2018)
The increasing application of lightweight metals in combination with a growth in the complexity of components provides new challenges to the numerical modeling of sheet materials. The choice of the material model and the associated mapping of the hardening behavior are of substantial importance for a realistic process prediction and the following spring back calculation in particular. The implementation of the Bauschinger-effect via isotropic-kinematic hardening laws can lead to a substantial improvement of the prediction quality. It is commonly known, that an accurate prognosis of sheet metal forming processes requires the consideration of the semi-finished products anisotropy. However, the identification of the Bauschinger-effect, which describes the reduction of the yield stress after a load reversal, and corresponding numerical models, is usually done under a specific stress state and in one direction of the sheet. Considering the vast variety of stress states and loading directions occurring in a forming operation, the anisotropic behavior of the Bauschinger-effect under uniaxial stress and its evolution during shearing is analyzed. Using a miniaturized tension-compression test, the cyclic hardening of the mild steel DX56 and the high strength steel DP600 and the aluminum alloy AA6016 is characterized in 0°, 45° and 90° to the rolling direction. By the identification of an isotropic-kinematic hardening law in combination with the anisotropic flow criterion Yld2000-2d the model's ability to extrapolate the hardening behavior is evaluated. In the last step, the transferability of parameters from the uniaxial stress state to results from a modified shear test is analyzed.
CRIS-Team Scopus Importer:2023-03-29